Footloose Conroy - McGinley, Marjorie M. (New York Avalon, 1999)
When the woman he loves betrays him, Michael Conroy rides away from the Texas ranch where he is foreman and heads into the New Mexico Territory. His plans to remain free of responsibility and entanglement quickly evaporate once a group of loyal ranch hands catch up to him. They are determined to follow his lead and to work alongside this honest, hardworking cowboy.
75005
Keywords: Western stories